Proteomic profiles for Alzheimer's disease and mild cognitive impairment among adults with Down syndrome spanning serum and plasma: An Alzheimer's Biomarker Consortium–Down Syndrome (ABC–DS) study. Issue 1 (30th June 2020) - Petersen, Melissa E.; Zhang, Fan; Schupf, Nicole; Krinsky‐McHale, Sharon J.; Hall, James; Mapstone, Mark; Cheema, Amrita; Silverman, Wayne; Lott, Ira; Rafii, Michael S.; Handen, Benjamin; Klunk, William; et al.
Abstract: Introduction: Previously generated serum and plasma proteomic profiles were examined among adults with Down syndrome (DS) to determine whether these profiles could discriminate those with mild cognitive impairment (MCI‐DS) and Alzheimer's disease (DS‐AD) from those cognitively stable (CS). Methods: Data were analyzed on n = 305 (n = 225 CS; n = 44 MCI‐DS; n = 36 DS‐AD) enrolled in the Alzheimer's Biomarker Consortium–Down Syndrome (ABC–DS). Results: Distinguishing MCI‐DS from CS, the serum profile produced an area under the curve (AUC) = 0.95 (sensitivity [SN] = 0.91; specificity [SP] = 0.99) and an AUC = 0.98 (SN = 0.96; SP = 0.97) for plasma when using an optimized cut‐off score. Distinguishing DS‐AD from CS, the serum profile produced an AUC = 0.93 (SN = 0.81; SP = 0.99) and an AUC = 0.95 (SN = 0.86; SP = 1.0) for plasma when using an optimized cut‐off score. AUC remained unchanged to slightly improved when age and sex were included. Eotaxin3, interleukin (IL)‐10, C‐reactive protein, IL‐18, serum amyloid A, and FABP3 correlated fractions at r 2 > = 0.90. Discussion: Proteomic profiles showed excellent detection accuracy for MCI‐DS and DS‐AD.